Lean enterprise systems : using IT for continuous improvement - Bell, Steve, 1960- (Hoboken : Wiley, 2006)
Table of Contents Foreword Preface : the goal of this book 1 Lean and IT : the human factor 2 Realizing the value of Lean 3 Three stages of Lean evolution 4 Fundamentals of production and inventory management 5 Lean planning and execution 6 Charting the Enterprise software universe 7 Integrating the value streams 8 Managing knowledge for competitive advantage 9 The event-driven Lean enterprise 10 Linking strategy with action : performance management 11 Lean IT : applying continuous improvement to information systems Postscript : Zen and the art of Lean